Soybean for Human Consumption and Animal Feed 2020
DOI: 10.5772/intechopen.89497
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Amino Acids in Health, Genetics, and Evaluation

Abstract: Soybean is an important source of protein and amino acids for humans and livestock because of its well-balanced amino acid profile. This chapter outlines the strengths and weaknesses of soybean as a complete amino acid source as well as the relative importance of individual amino acids. Special attention is paid to the sulfur-containing amino acids, methionine and cysteine. Breeding and genetic engineering efforts are summarized to highlight previous accomplishments in amino acid improvement and potential aven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Moreover, both leucine and isoleucine play vital roles in glucose consumption by regulating muscular glucose transporters . Besides, sulfur-containing amino acids such as methionine and/or cysteine critically affect the evaluation of soybean seeds as dietary supplements and play vital role for synthesis of macromolecules such as protein, , and deficient of these amino acids negatively affect growth, disease immunity, and breast muscle development, among others, to human and animals. , Thus, so far, our study suggested that a high level of particular essential amino acids generated by water soaking at 55 °C might create suitable nutritional foundation of dietary supplements for human and livestock.…”
Section: Results and Discussionmentioning
confidence: 68%
“…Moreover, both leucine and isoleucine play vital roles in glucose consumption by regulating muscular glucose transporters . Besides, sulfur-containing amino acids such as methionine and/or cysteine critically affect the evaluation of soybean seeds as dietary supplements and play vital role for synthesis of macromolecules such as protein, , and deficient of these amino acids negatively affect growth, disease immunity, and breast muscle development, among others, to human and animals. , Thus, so far, our study suggested that a high level of particular essential amino acids generated by water soaking at 55 °C might create suitable nutritional foundation of dietary supplements for human and livestock.…”
Section: Results and Discussionmentioning
confidence: 68%
“…The author concluded that there was no significant correlation between the tofu hardness and the 11S:7S ratio. Both positive and negative correlations between the 11S:7S storage protein ratios and tofu hardness were reported by different group of researchers (Singer, Zhang, Mian, & Huang, 2019).…”
Section: Storage Protein Compositionmentioning
confidence: 76%
“…Methionine and cysteine are considered essential amino acids, as they are not produced in the human body, and therefore must be acquired through one’s diet. Its consumption is essential for the biosynthesis of many molecules important for the correct performance of various organisms, such as creatine, carnitine, polyamines, epinephrine, choline, and melatonin [ 38 , 39 ]. Furthermore, in the biosynthesis of sulfur amino acids, the product, S-adenosylmethionine, is a precursor for the methylation of monolignols, an essential process for lignin formation [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme is also involved in methionine recovery through the formation of the L-homocysteine product via de novo methionine synthesis [ 45 ]. Deficiency in one or more amino acids is sufficient to negatively impact the growth and development of different organisms [ 38 ]. Therefore, one of the focuses of genetic improvement has been to enrich the composition of the amino acids present in soybeans and not just the crude protein content itself.…”
Section: Resultsmentioning
confidence: 99%